2020
DOI: 10.1080/15476286.2020.1729584
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular tRNAs and tRNA-derived fragments

Abstract: Fragmentation of tRNAs generates a family of small RNAs collectively known as tRNA-derived fragments. These fragments vary in sequence and size but have been shown to regulate many processes involved in cell homoeostasis and adaptations to stress. Additionally, the field of extracellular RNAs (exRNAs) is rapidly growing because exRNAs are a promising source of biomarkers in liquid biopsies, and because exRNAs seem to play key roles in intercellular and interspecies communication. Herein, we review recent descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 175 publications
(313 reference statements)
2
65
0
1
Order By: Relevance
“…The transcriptomics of EVs, including signature of EV-derived microRNAs and RNA-derived fragments, is disputed as a promising source of biomarkers in liquid biopsies (142). Future studies that could clearly explain the potency of EVs as biomarkers for personalized care of HF are required.…”
Section: Future Directions and Challenges In Ev Researchmentioning
confidence: 99%
“…The transcriptomics of EVs, including signature of EV-derived microRNAs and RNA-derived fragments, is disputed as a promising source of biomarkers in liquid biopsies (142). Future studies that could clearly explain the potency of EVs as biomarkers for personalized care of HF are required.…”
Section: Future Directions and Challenges In Ev Researchmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) can be released to circulate in the peripheral blood. Circulating levels of tRFs could be useful as biomarkers of some diseases and surrogate measures of disease progression [13,14], indicating their potential use in diagnosis and assessment of I/R in pediatric intussusception. In our previous studies, we found I/R in both our animal models and our pediatric intussusception patients.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of tRFs can uctuate in response to stimuli. Circulating levels of tRFs might be useful as the surrogate measurements of disease progression [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…When combined with cytochrome C, tRFs inhibit the formation of apoptotic bodies. Finally, studies have shown that tRF exists in hematopoietic cells, lymphocytes, and the blood circulation system, suggesting that these fragments may play a role in immune response [11][12][13].…”
Section: Introductionmentioning
confidence: 99%